2012
DOI: 10.4236/cm.2012.32016
|View full text |Cite
|
Sign up to set email alerts
|

“Qi-Invigorating” Chinese Tonic Herbs (<i>Shens</i>) Stimulate Mitochondrial ATP Generation Capacity in H9c2 Cardiomyocytes <i>in Situ</i> and Rat Hearts <i>ex Vivo</i>

Abstract: In the study, using ethanol extracts of Renshen (Panax ginseng C A Meyer), Xiyangshen (Panax quinquefolius L.) and Dangshen (Codonopsis pilosulae), we investigated the effect of these "Qi-invigorating" Chinese tonic herbs on mitochondrial ATP generation capacity (ATP-GC) in H9c2 cardiomyocytes in situ and rat hearts ex vivo. All three types of "Shens" stimulated mitochondrial ATP-GC, with Renshen being most potent. While a parallel enhancement in mitochondrial ATP-GC was observed in Renshen-and Xiyangshen-pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…In addition, a recent study has shown that Qi-invigorating herbs can increase the energy charge in cultured rat myocytes as well as in rat skeletal muscle [4]. Consistent with this, a previous study in our laboratory has found that the three Qi-invigorating herbs (DS, RS and XYS) can increase adenosine triphosphate (ATP)-generation capacity (ATP-GC) in cultured H9c2 cardiomyocytes [5]. Interestingly, DS, RS and XYS differ in the nature of their meridian tropism, in which DS and RS but not XYS can act through the "Spleen" meridian.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, a recent study has shown that Qi-invigorating herbs can increase the energy charge in cultured rat myocytes as well as in rat skeletal muscle [4]. Consistent with this, a previous study in our laboratory has found that the three Qi-invigorating herbs (DS, RS and XYS) can increase adenosine triphosphate (ATP)-generation capacity (ATP-GC) in cultured H9c2 cardiomyocytes [5]. Interestingly, DS, RS and XYS differ in the nature of their meridian tropism, in which DS and RS but not XYS can act through the "Spleen" meridian.…”
Section: Introductionsupporting
confidence: 55%
“…According to TCM theory, the three "Shen" herbs (DS, RS and XYS) are traditionally used for Qi-invigoration, which can be viewed in terms of an up-regulation of energy status as well as the stimulation of growth and development of the human body [2]. A previous study in our laboratory has demonstrated that the "Shen" herbs under investigation are able to increase ATP-GC in cultured H9c2 cardiomyocytes [5]. Results obtained in the present study showed that the three "Shen" ethanolic extracts stimulated the proliferation of primary splenocytes in vitro and increased ATP-GC in cultured Caco 2 colon epithelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other study also demonstrated significant increases in ATP in H9c2 cardiomyocytes in vitro when supplemented with Panax ginseng . 6 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Qi-invigorating herbs including Panax ginseng can affect mitochondria energy production 6 and antioxidant capacity. 7 The active ingredients such as polysaccharide and ginsenoside in Panax ginseng extracts played an important role in alleviating cellular oxidative stress through either the reduction in ROS levels, 8 or protection from lipid peroxides and increase in SOD levels.…”
Section: Introductionmentioning
confidence: 99%
“…Qi in the TCM system and mitochondria in modern medicine system play similar roles in providing power for cells and promoting the transformation of material and energy [3], and therefore, a connection between the mitochondria and Qi has been suggested [4] [5] [6]. In addition, many researchers have proposed that there is a great deal of similarity in their characteristics and functions between Qi and mitochondria [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%